Isolation and Identification of Vancomycin-Resistant Enterococcus Faecalis - S. Kadhem, Haider; T. Flayyih, May (Iraqi Journal of Science, 2025)
One hundred thirty - five clinical specimens of urine, blood, teeth root canal and burns were obtained from patients in hospitals of Baghdad. The specimens were cultured on Pfizer Selective Enterococcus agar to purify Enterococci isolates. 20 E. faecalis isolates were identified biochemically by growing in 10Cº, 45Cº, 6.5% NaCl, at pH 9.6 and confirmed by VITEK. Determination of Vancomycin-Resistant E. faecalis isolates were done by the minimum inhibitory concentrations [MICs] using agar dilution method. Seventeen E. faecalis isolates were determined as Vancomycin-Resistant and Intermediate Resistant.